2019
DOI: 10.3390/cancers11121925
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration in Muscle Mass and Physical Function Differs According to Weight Loss History in Cancer Cachexia

Abstract: Background: Muscle mass and physical function (PF) are common co-primary endpoints in cancer cachexia trials, but there is a lack of data on how these outcomes interact over time. The aim of this secondary analysis of data from a trial investigating multimodal intervention for cancer cachexia (ClinicalTrials.gov: NCT01419145) is to explore whether changes in muscle mass and PF are associated with weight loss and cachexia status at baseline. Methods: Secondary analysis was conducted using data from a phase II r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Cancer accelerates the decline process owing to its chronic consumptive characteristics for resulting syndromes or diseases such as fatigue, cancer cachexia, and sarcopenia. [4][5][6] Recently, HGS was recommended to be a criterion in the definition of cancer cachexia. 7 More strikingly, HGS replaced the muscle mass as the primary criterion to define sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer accelerates the decline process owing to its chronic consumptive characteristics for resulting syndromes or diseases such as fatigue, cancer cachexia, and sarcopenia. [4][5][6] Recently, HGS was recommended to be a criterion in the definition of cancer cachexia. 7 More strikingly, HGS replaced the muscle mass as the primary criterion to define sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…The HGS of cancer patients was different from that of the healthy populations. Cancer accelerates the decline process owing to its chronic consumptive characteristics for resulting syndromes or diseases such as fatigue, cancer cachexia, and sarcopenia 4–6 . Recently, HGS was recommended to be a criterion in the definition of cancer cachexia 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of muscle mass loss in the control arm in this study does not evoke a corresponding reduction in HGS. Low muscle mass is associated with reduced physical function; however, the relationship is nonlinear and, likely, there is a variable impact on physical function outcomes depending on the magnitude of changes in muscle mass ( 14 ). The potential of physical function outcomes such as HGS (and other performance testing) to detect change relative to muscle/weight changes in cancer cachexia remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Handgrip strength (HGS) (kg) was collected at baseline and after 6 weeks and measured with a hydraulic handheld dynamometer (JAMAR). The test was performed using the dominant hand, and three test trials were performed ( 7 , 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…In spite of a linear correlation between the two reported by some authors [ 26 ], others failed to demonstrate it. Results from the latter studies instead showed preserved muscle function in the early stages of the disease, in spite of significant muscle loss and a prevalent decline during the late stage of cachexia prior to minor loss of muscle mass [ 62 ]. Thus, the heterogeneity of study populations in terms of cancer type and stage and baseline nutritional status could hamper conclusions when comparing the results of different trials.…”
Section: Discussionmentioning
confidence: 99%